Shifting towards Communication Service Provider (CSP) to Digital Service Provider (DSP): an analysis on the context of Grameenphone Limited - Mawa, Jannatul (BRAC University, 2016)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2016.